What is the impact of flexicurity on the chances of entry into employment for people with low education and activity limitations due to health problems? A comparison of 21 European countries using Qualitative Comparative Analysis (QCA) - Mona C Backhans; Sarah Mosedale; Daniel Bruce; Margaret Whitehead; Bo Burström (BMC, 2016)
Abstract Background Employment and unemployment are key determinants of health inequalities and should be a priority when discussing policies to reduce such inequalities. Our aim is to investigate how flexicurity policies across European countries impact on the employment chances for people with low education and activity limitations. Methods The longitudinal EU-SILC dataset, pooled 2005-2010, was used to calculate labour market outcomes. The sample consisted of 25 countries and 19,881 individuals. The employment transitions of non-employed people with activity limitations was followed from one year to the next, and the outcomes were rates of return-to work (RTW) among those with low education, and relative equality of RTW between those with low and high education (rate ratio, RR). Data on flexicurity policy and labour market factors were accessed from Eurostat and the OECD. As policy data was only available for OECD countries, the sample was reduced to 21 countries. Fuzzy-set QCA (Qualitative Comparative Analysis) was used to examine how different combinations of the components of flexicurity were linked to the two outcomes. Results Where high rates of RTW were achieved, high employment rates were always present. In five countries (the Nordic countries and the Netherlands) these factors coexisted with high expenditure on active labour market policies and social services in old age. In three others (The Czech Republic, UK and Estonia) they were combined with low employment protection and low benefit expenditure. For equality in RTW, low unemployment rates were combined with either high benefit expenditure, or low employment protection. Conclusion We found two routes that lead to high RTW: we characterise these as the high road and the low road. Taking the low road (relaxing employment protection and limiting benefits) may be a tempting option for poorly performing countries. However, without measures to stimulate female employment it may not be enough as high overall employment is so important in enabling people with activity limitations to access the labour market. To achieve equality in RTW, it seems that as long as unemployment is low, either flexibility or security is sufficient.